Counseling Guidance Program Development in Indonesian Elementary Schools - Heri Febri Yadi; Firman Firman; Neviyarni Neviyarni; Muhammad Asyraf bin Che Amat (UIN Siber Syekh Nurjati Cirebon, 2023)
This study aims to find out and understand the importance of the counseling program in elementary schools (SD), aiming to produce individuals achieving optimal development in accordance with their potential, interests and values that become their way of life, many elementary schools (SD) currently have guidance and counseling services not implemented , and there is no guidance counseling program with class teachers, because elementary school (SD) teachers lack knowledge of counseling guidance programs. The implementer of the BK program in SD is the class teacher in charge of carrying out guidance and counseling services in the class for which he is responsible. This research is a qualitative research with the method of literature review which is used as a reinforcement of the literature that is relevant to the things you want to study. Development of counseling guidance programs in elementary schools (SD). Guidance and counseling programs in elementary schools greatly influence the development of students' potential, interests and talents. So from this the guidance and counseling program in elementary schools (SD) must be considered so that the provision of services to students is also effective and the results are in accordance with what is desired.